Influenza B-related meningoencephalitis in adults. (21st June 2018) - Yong, Chen Han; Vallat, Wilson; Norton, Graham
Abstract : We present a case involving an 85-year-old man with acute confusion and new onset seizure following a 1-week history of respiratory prodrome. This case report describes a case of influenza B-related meningoencephalitis supported by evidence of an influenza B infection and temporal relation of the neurological event and respiratory illness in the absence of other identifiable cause. Diagnosis is guided by cerebrospinal fluid profile and nasopharyngeal PCR. Treatment is largely supportive and the effect of vaccination on prevention of this neurological complication remains unclear.